BuyFind

Precalculus: Mathematics for Calcu...

6th Edition
Stewart + 5 others
Publisher: Cengage Learning
ISBN: 9780840068071
BuyFind

Precalculus: Mathematics for Calcu...

6th Edition
Stewart + 5 others
Publisher: Cengage Learning
ISBN: 9780840068071

Solutions

Chapter 1.4, Problem 79E
To determine

To calculate: The expression 3(1+x)13x(1+x)23(1+x)23

Expert Solution

Answer to Problem 79E

  3(1+x)13x(1+x)23(1+x)23=2x+3(1+x)43

Explanation of Solution

Given information:

Given expression is 3(1+x)13x(1+x)23(1+x)23

Consider the expression as 3(1+x)13x(1+x)23(1+x)23

Now,

  3(1+x)13x(1+x)23(1+x)23=3(1+x)13x(1+x)23(1+x)23=3(1+x)13+23x(1+x)23(1+x)23=3(1+x)x(1+x)23+23=3+3xx(1+x)43=2x+3(1+x)43

Therefore, simplest form of the expression 3(1+x)13x(1+x)23(1+x)23=2x+3(1+x)43

Have a homework question?

Subscribe to bartleby learn! Ask subject matter experts 30 homework questions each month. Plus, you’ll have access to millions of step-by-step textbook answers!